233k views
2 votes
Y−1=−2(x−2) in slope intercept form

User Jkebinger
by
4.6k points

2 Answers

2 votes

Explanation:

Hey there!

We know;

The slope intercept form of equation is;

y = mx+c

So, let's try to take it in this form.

(y-1) = -2(x-2)

Multiply -2 and (x-2)

(y-1) = -2x + 4

Take '-1' to right side.

y = -2x+4+1

y = -2x+5

Therefore, the equation is y = -2x+5.

Hope it helps...

User Sysuser
by
4.9k points
6 votes

Answer:


y = - 2x + 5

Explanation:

Simply simplify the equation from what it is to the slope intercept format:


y = mx + b

User Pismotality
by
5.2k points